Tracing Mumps in Rural Area: A Clinical Profile of Infected Children and Adolescents in Bulu, Tuban - Dion, Aldy; Pribadi, Florence; Dewi, Karina (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2025)
Mumps, also known as epidemic parotitis, is a viral infection that affects the salivary glands. This disease commonly occurs among school-aged children and adolescents. According to data from the World Health Organization (WHO), the incidence of mumps in Southeast Asia (excluding Indonesia) reached 8,985 cases in 2022. In Indonesia, the Ministry of Health reported 6,593 cases in 2024. Given these challenges and the high number of cases found in the community, researchers aimed to study the clinical profile of mumps in school-aged children and adolescents in Bulu, Tuban. This research was observational in nature, using a descriptive cross-sectional study design. The findings revealed that male children are at higher risk of contracting mumps, with the highest infection rate observed in the 8-10 year age group. Areas characterized by close-knit living conditions and low immunization coverage reported a higher incidence of mumps. The most common complaint that led patients to seek medical care was cheek pain. Additionally, a significant number of mumps patients were found to be underweight. The most frequently administered treatment involved a combination of analgesic and vitamin.